2007
DOI: 10.1038/modpathol.3800712
|View full text |Cite
|
Sign up to set email alerts
|

Frequent homogeneous HER-2 amplification in primary and metastatic adenocarcinoma of the esophagus

Abstract: HER-2 is the target for antibody based treatment of breast cancer (Herceptin s ). In order to evaluate the potential role of such a treatment in esophageal cancers, HER-2 amplification and overexpression was investigated in primary and metastatic cancers of the esophagus. A tissue microarray was constructed from 255 primary esophageal cancers (110 adenocarcinomas and 145 squamous cell carcinomas), 89 nodal and 33 distant metastases. Slides were analyzed by immunohistochemistry (HercepTestt; DAKO) and fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
142
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 56 publications
19
142
3
Order By: Relevance
“…12 In a large study by a different group, the rate of ErbB2 overexpression/amplification was 15%, and no prognostic impact with respect to patients' survival could be demonstrated. 13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…12 In a large study by a different group, the rate of ErbB2 overexpression/amplification was 15%, and no prognostic impact with respect to patients' survival could be demonstrated. 13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 95%
“…11,13,15 In this study, we tested ErbB2 status in oesophageal adenocarcinomas by in situ hybridisation (amplification) and immunohistochemistry (expression). A rate of ErbB2 positivity, which was defined 3 þ by immunohistochemistry and/or an ErbB2/Chr17 quotient of Z2 as assessed by in situ hybridisation, could be detected in 29% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, Her2/neu overexpression and/or amplification has been observed, not only in breast cancers, but also in colon (1), bladder (2), ovarian (3), endometrial (4), lung (5), uterine cervix (6), head and neck (7), esophageal (8), and gastric carcinomas (9). The Her2/neu protein has also been reported to be overexpressed in 10-30% of patients with gastric cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%